Modelling costs and outcomes of newborn hearing screening: The economic part of a German health technology assessment project - Franz Hessel; Eva Grill; Petra Schnell-Inderst; Jürgen Wasem (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2002)
The prevalence of newborn hearing disorders is 1-3 per 1000. Crucial for later outcome are correct diagnosis and effective treatment in the first year of life. With BERA and TEOAE low-risk techniques for early detection are available. Universal screening is recommended but not realised in most European health care systems. Objective of the study was to examine the scientific evidence of newborn hearing screening, thus to compare cost-effectiveness of different programmes, differentiated by type of strategy (risk screening, universal screening, no screening). Methods: In an interdisciplinary health technology assessment project all relevant studies on newborn hearing screening were identified and data on medical outcome, costs and cost-effectiveness extracted. A Markov model was designed to calculate cost-effectiveness ratios. Results: Economic data were extracted from 20 relevant publications. In the model total costs for screening of 100.000 newborns with a time horizon of ten years were calculated: 2.0 Mio. exteuro for universal screening (U), 1.0 Mio. exteuro for risk screening (R) and 0.6 Mio. exteuro for no screening (N). The costs per child detected: 13,395 exteuro (U) respectively 6,715 exteuro (R) and 4,125 exteuro (N). Conclusions: A remarkable small number of economic publications mainly of low methodo-logical quality was found. In our own model we found reasonable cost-effectiveness ratios also for universal screening. Considering the outcome advantages of higher numbers of cases detected a universal newborn hearing screening is recommended.
Keywords: 330; Elektromedizinisches Gerät; Technikbewertung; Kosten-Nutzen-Analyse; Theorie; Deutschland